Strategi Pengembangan Usaha dengan Diversifikasi dan Endorsement dalam Upaya Pengembangan Produk Sate Taichan Bang Deeps - Muhammad Rifqi Awalludin; Rohandi, Mochamad Malik Akbar; Permana, Rezi Muhamad Taufik (Bandung Conference Series: Business and Management, 2024)
Abstract. MSMEs in the city of Bandung were recorded at 10,181 based on this data, the Culinary industry is a very rapid industry compared to other industries, which is 40%. One of the businesses in the culinary field in the city of Bandung is Sate Taichan Bang Deeps, which is a brand engaged in culinary, especially spicy food. In general, satay is processed meat that uses peanut sauce. Following the current development, satay has several kinds of olahanan such as taichan satay which is processed chicken meat and uses chili sauce to add to the flavor of the satay. Sate Taichan Bang Deeps has a main menu, namely taichan satay which is processed chicken meat. The number of competitors with similar products, Sate Taichan Bang Deeps carries out a product diversification strategy, namely bringing up new products in the form of rice bowls which have several variants such as oseng taichan, krispy sambal taichan and krispy sambal matah. Sate Taichan Bang Deeps uses SWOT Analysis, Porter's Five Forces, Balance Scorecard, Target and Performance, and BCG (Boston Consulting Group) strategies which aim to evaluate and design strategies in business development to achieve targets. Abstrak. UMKM di Kota Bandung tercatat sebanyak 10.181 berdasarkan data tersebut industri Kuliner merupakan industri yang sangat pesat dibanding industri lainnya yaitu sebesar 40%. Salah satu usaha dibidang kuliner di kota Bandung yaitu Sate Taichan Bang Deeps yang merupakan suatu brand yang bergerak dibidang kuliner khususnya makanan pedas. Pada umunya, sate merupakan olahan daging yang memakai bumbu kacang. Mengikuti perkembangan saat ini, sate mempunyai beberapa macam olahanan seperti sate taichan yang merupakan daging ayam olahan dan memakai sambal untuk menambah cita rasa dari sate tersebut. Sate Taichan Bang Deeps memiliki menu utama yaitu sate taichan yang merupakan olahan daging ayam. Banyaknya pesaing dengan produk serupa, Sate Taichan Bang Deeps melakukan strategi diversifikasi produk yaitu memunculkan produk baru berupa rice bowl yang memiliki beberapa varian seperti, oseng taichan, krispy sambal taichan dan krispy sambal matah. Sate Taichan Bang Deeps menggunakan strategi SWOT Analysis, Five Forces Porter, Balance Scorecard, Target and Performance, dan BCG (Boston Consulting Group) yang bertujuan guna mengevaluasi serta merancang strategi dalam pengembangan usaha untuk mencapai target.